Nucleobase and nucleoside transport and integration into plant metabolism - Girke, Christopher; Daumann, Manuel; Niopek-Witz, Sandra; Möhlmann, Torsten (Frontiers in Plant Science, 2014)
Nucleotide metabolism is an essential process in all living organisms. Besides newly synthesized nucleotides, the recycling (salvage) of partially degraded nucleotides i.e. nucleosides and nucleobases serves to keep the homeostasis of the nucleotide pool. Both types of metabolites are substrates of at least six families of transport proteins in Arabidopsis thaliana (Arabidopsis) with a total of 49 members. In the last years several members of such transport proteins have been analyzed allowing to present a more detailed picture of nucleoside and nucleobase transport and the physiological function of these processes. Besides functioning in nucleotide metabolism it turned out that individual members of the before named transporters exhibit the capacity to transport a wide range of different substrates including vitamins and phytohormones. The aim of this review is to summarize the current knowledge on nucleobase and nucleoside transport processes in plants and integrate this into nucleotide metabolism in general. Thereby, we will focus on those proteins which have been characterized at the biochemical level.